Longitudinal research of calf muscles functional changes for healthy and with Achilles tendon rupture subjects - Aleknavičiūtė-Ablonskė, Vaida; Skurvydas, Albertas (Social Welfare: Interdisciplinary Approach, 2013)
Achilles tendon is the strongest tendon in human body, but despite that, it is also one of the common ruptured tendons. When the Achilles tendon rupture (ATR) occurs, strength of calf muscles, proprioception, and postural stability always decrease. It is well known that rehabilitation infuences the greater recovery after Achilles tendon rupture, but despite that the probability of the Achilles tendon re-rupture one year follow up still remains. Therefore, it is very important to understand the ruptured Achilles tendon and calf muscles healing possibilities not only after applied physiotherapy, but also one year follow up. During the present longitudinal research calf muscles strength and proprioception changes of a healthy person and a person with ATR were examined.
Keywords: muscle torque variability; isometric maximal voluntary contraction torque; visual feedback